Análise da dinâmica da carga moedora nos moinhos de bolas - Dirceu Valadares Nascimento (2013)
Comminution is a set of operations to achieve size reduction for a material, from large mined blocks (ROM Run of Mine), to the smallest size required for liberation of useful material from that of no economic value. Among numerous equipments employed in this operation, tumbling mills are the most commonly used in the final stages of comminution process. These devices consist of a large cylindrical shell horizontally oriented, lined with a protection layer and filled with a grinding charge and the material being processed. The charge dynamics in a ball mill is investigated by computer simulation using Rigid Body Dynamics method. The lining shape, ball size distribution of and rotation speed are evaluated for power consumption and impacts dynamics between balls and balls-shell.